Adenomatoid odontogenic tumor with dentigerous cyst: Report of a rare case with review of literature - Vikramjeet Singh; Sunder Goyal; Soheyl Sheikh; P Shambulingappa; Balwinder Singh; Ravinder Singh (Wolters Kluwer Medknow Publications, 2012)
Adenomatoid odontogenic tumor (AOT) is a benign lesion derived from the complex system of dental lamina or its remnant. It is categorized into three variants (follicular, extrafollicular, and peripheral). We present a rare case of AOT arising from a dentigerous cyst around the unerupted canine in a 28-year-old female. We believe that this case z an odontogenic cyst with neoplastic development, containing both epithelial and mesenchymal components. As more cases accumulate, we will be able to study these rare lesions further whether the AOTs derived from an odontogenic cyst could represent a distinct "hybrid" variant separate to the three variants described thus far.